The relationship between leadership behaviour and organizational commitment on quality management practices among administrative officers in International Islamic University Malaysia (IIUM) / Ilmyzat Ismail - Ismail, Ilmyzat (2014)
Studies have shown that the practice of quality management could be actualized when the organization is led by effective leaders and having committed workforce. However, to what extent this is true in the context of local settings such as International Islamic University Malaysia (IIUM) where quality culture gradually being nurtured since its inception for enhancing existing processes of teaching and learning as well as research activities Thus, this study was carried out to examine the relationship of leadership behaviour and organizational commitment on quality management among the administrators of International Islamic University Malaysia. This study employed a quantitative approach using a survey method by adopting a combination of three established instruments developed by Bass and Avolio (1995), Meyer and Allen (1993) and Zeitz, Johannesson and Ritchie Jr. (1997). A total of 118 administrative officers from the main campus and branch campuses throughout Klang Valley were randomly selected to participate in this study. Using both descriptive and inferential statistical method, the findings revealed that the administrative officers perceived that their superiors in IIUM exhibited more transformational leadership behaviour rather than transactional leadership behaviour. The findings also revealed that IIUM administrative officers perceived that they have high level of organizational commitment especially for both affective and normative commitment dimensions. Besides that, quality management practices in IIUM were perceived as high by most of administrative officers. The study also found both independent variables namely organizational commitments and leadership behaviour could influence quality management practices. Finally, the results displayed that organizational commitment contributed 32.6% to the variance of quality management practices. This study implied that building organizational commitment could contribute to effective and successful practices of quality management in the university.